Modeling business objects with XML schema - Daum, Berthold, 1949- (San Francisco, Calif. : Morgan Kaufmann ; Heidelberg, Germany : Dpunkt.verlag, 2003)
The art of writing XML schema in a systematic way.
Foundations -- Conceptual modeling -- Everybody likes jazz -- XML basics -- XML schema -- Authoring XML schema -- Relax NG -- From conceptual model to schema -- Validation beyond XML schema -- Reality check : the world is object-oriented -- Reality check : the world is relational -- Schema evolution -- Schemata in large environments -- Outlook.
"Copublished by Morgan Kaufmann Publishers and dpunkt.verlag"--T.p. verso.
Includes bibliographical references (p. 503-506) and index.
Keywords: XML (Document markup language); Electronic books